TAX AND MICRO, SMALL AND MEDIUM ENTERPRISES: DEVELOPMENT AND FUTURE RESEARCH DIRECTIONS BASED ON BIBLIOMETRIC STUDY - Hartanto, Hartanto; Pramuka, Bambang Agus (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to map the development and direction of research on tax and MSMEs and gain insight into future research prospects. The analysis was carried out based on the bibliometric method with the support of Publish or Perish and VOSviewer software and the Google Scholar database. Data was processed on the metadata of research publications from 2000 to 2022 across 998 journals. The results show that journal publications commenced in 2006, with fluctuating trends until 2016. Post-2016, there is consistent growth, with the highest spike of 280% in 2012 and a notable dip of -28.57% in 2011. Geographically, the research landscape is predominantly situated in Asia and Africa, with significant contributions from Indonesia, India, and Nigeria. India emerges as a standout, both in terms of prolific researchers and extensive collaborations. The network visualization of terms identifies eight distinct clusters, with emerging themes encompassing the profound impact of the COVID-19 pandemic, the transition towards a new normal, issues about empowerment and sustainability, and the crucial aspect of MSME tax compliance.